2021
DOI: 10.1037/bul0000335
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of external attentional focus for motor performance and learning: Systematic reviews and meta-analyses.

Abstract: Considerable literature on the role of attentional focus in motor performance and learning has accumulated for over two decades. We report the results of comprehensive meta-analyses that address the impact of an external focus (EF, on intended movement effects) versus internal focus (IF, on movements of body parts) of attention on the performance and learning of motor skills. Values of effect sizes (ES) from 73 studies with 1,824 participants and 40 studies with 1,274 participants were used for examining the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
77
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 265 publications
(302 reference statements)
12
77
1
Order By: Relevance
“…In this study, our participants appeared to successfully modulate their gait speed during a single-day session when provided concurrent visual feedback and an external focus by the MR-HMD. Our findings align with substantial evidence supporting an external focus to promote motor performance and learning (Wulf, 2013 ; Chua et al, 2021 ). Our results also align with previous research which reports the benefits of extrinsic visual cues on motor learning in healthy individuals (Todorov et al, 1997 ; Sigrist et al, 2013 ; Lewthwaite and Wulf, 2017 ) and persons with physical disability (Aung and Al-Jumaily, 2014 ).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, our participants appeared to successfully modulate their gait speed during a single-day session when provided concurrent visual feedback and an external focus by the MR-HMD. Our findings align with substantial evidence supporting an external focus to promote motor performance and learning (Wulf, 2013 ; Chua et al, 2021 ). Our results also align with previous research which reports the benefits of extrinsic visual cues on motor learning in healthy individuals (Todorov et al, 1997 ; Sigrist et al, 2013 ; Lewthwaite and Wulf, 2017 ) and persons with physical disability (Aung and Al-Jumaily, 2014 ).…”
Section: Discussionsupporting
confidence: 90%
“…The finding of attentional focus differences during retention or transfer, but not during acquisition, has been previously reported for a balance task (Wulf et al, 1998; 2001a, 2001b; Chiviacowsky et al, 2010) and a dart-throwing task (Lohse et al, 2010). It is also noteworthy that a recent meta-analysis (Chua et al, 2021) found larger effects for attentional focus differences in retention than acquisition, and in transfer than retention.…”
Section: Discussionmentioning
confidence: 96%
“…What performers concentrate on while preparing for and executing a motor skill matters; what target one intends to hit, rather than how to move the body to achieve it, affects success. A considerable literature examining the role of attentional focus on motor performance and learning has accumulated over the past two decades (Chua et al, in press; Wulf, 2013). This line of research has demonstrated that an external focus of attention, or concentration on the intended effect of the movement (e.g., planned trajectory of a ball, stability of a balance platform, sound to be produced), results in better performance and learning than does an internal focus, or concentration on body movements.…”
Section: Optimal Motor Learningmentioning
confidence: 99%